Indoor environmental quality of green office buildings in China: Large-scale and long-term measurement. (March 2019) - Geng, Yang; Lin, Borong; Yu, Juan; Zhou, Hao; Ji, Wenjie; Chen, Hongzhong; Zhang, Zhongchen; Zhu, Yingxin
Abstract: This study aims to explore the actual indoor environmental quality (IEQ) in Chinese green office buildings, based on the large-scale and long-term measurement data. A total of 41 green office buildings throughout Cold zone, Hot-Summer-Cold-Winter (HSCW) zone and Hot-Summer-Warm-Winter (HSWW) zone were measured with 198 integrated environmental sensors from June, 2017 to August, 2018. The key findings of this study can be summarized as follows: 1) Indoor thermal comfort did not show a significant difference between climate zones in summer, while thermal environment of Cold zone was much warmer and drier than the counterpart of HSCW and HSWW zone in winter. The overall indoor thermal environment met the standard, although several thermal problems were found; 2) Indoor CO2 concentration was relatively high in summer or winter and low in transition seasons. The median values of indoor CO2 concentration were far below the threshold of 1000 ppm; 3) Indoor PM2.5 concentration was generally lower in HSWW zone and higher in winter. The median values of indoor PM2.5 concentration generally conformed to the standard guideline; 4) The median values of illuminance ranged from 340 lux to 522 lux and all of them reached the lower limit of 300 lux for common offices. The above results were compared with other findings from previous literature and several differences were illustrated. In addition, the correlations between indoor and outdoor environment were found. Other possible factors influencing IEQ were discussed qualitatively. Highlights: Indoor environmental quality in Chinese green office buildings was measured. 41 green office buildings were measured with 198 sensors for more than one year. The IEQ results vary in different seasons and climate zones. The overall IEQ performance in Chinese green office buildings meets the standard. IEQ can be influenced by outdoor weather, building operation and human factors.